Effects of Fuyou Formula on GnRH Secretion and Related Gene Expression in Treating Precocious Puberty - Zhang, Yi; Sun, Ning; Zhang, Meng; Ding, Qian; Wang, Qian; Liang, Yuguang; He, Huan; Yang, Yuxin; Guo, Chunyan (Frontiers in Pharmacology, 2022)
Fuyou (Fy) formula is an in-hospital preparation which consists of traditional Chinese medicine (TCM) that have been used for treating precocious puberty (PP) for over 20 years. In this study, we aim to clarify the effect of Fy formula and its major components in PP. To confirm the effect of Fy formula on the release of hypothalamic gonadotropin releasing hormone (GnRH), GT1-7 cells were treated with estrogen to build the model group, and subsequently treated with Fy formula and its major components to explore their effects on the secretion of GnRH. The level of the GnRH in GT1-7 cell lines were determined by ELISA. The results illustrated that compared to the model group, Fy formula appears to inhibit the release of GnRH. Also, mRNA expressions of the proteins that related to the GnRH secretion including GnRH, gonadotrophin-releasing hormone receptor (GnRHR), Kiss-1 metastasis-suppressor (Kiss1), G-protein coupled receptor 54 (GPR54), estrogen receptor α (ERα), insulin-like growth factors-1 (IGF-1) and insulin-like growth factors-1 receptor (IGF-1R) were detected by RT-PCR. The results demonstrated that Fy formula significantly reduce level of GnRH secretion in the GT1-7 cell lines compared with the model group. Moreover, it can significantly downregulate the expression of GnRH, GnRHR, Kiss1, GPR54, ERα, IGF-1 and IGF-1R. In summary, our results indicated that Fy formula and its major components may eliminate effects caused by estrogen, in which alleviate PP through the transcriptional regulation of target genes.